Efektivitas Sistem Aplikasi Elektronik BUMDes Sugihwaras (e-BES) dalam Pengelolaan Badan Usaha Milik Desa (BUMDes) di Desa Sugihwaras Kecamatan Candi Kabupaten Sidoarjo - Nur Febrianti; Eva Hany Fanida (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Digital transformation in village governance has encouraged Village-Owned Enterprises (Badan Usaha Milik Desa or BUMDes) to adopt information technology-based systems to improve the effectiveness of business management and public service delivery. One such innovation is the Sugihwaras Electronic BUMDes (e-BES) application, developed by the "Sukses Bersama" BUMDes in Sugihwaras Village, Candi District, Sidoarjo Regency, as a digital platform for marketing micro, small, and medium enterprise (MSME) products and providing digital transaction services. This study aims to analyze the effectiveness of the e-BES application in the management of BUMDes in Sugihwaras Village. A qualitative descriptive approach was employed. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data display, and conclusion drawing techniques. The analysis of system effectiveness was based on the framework proposed by Aprilia et al. (2014), which consists of eight dimensions: the role of the system, the role of government, system objectives, accessibility, system content, system interaction, supporting factors, and inhibiting factors. The findings indicate that the implementation of the e-BES application in BUMDes management has not yet been fully effective. Although the application has improved access to information, facilitated the marketing of MSME products, and supported digital-based public services, its implementation continues to face several challenges, including limited human resource capacity in system management, gaps in digital literacy among community members, prolonged system maintenance, inadequate public outreach, and application features that remain under development.